Marx's Rebellion Against Lenin - Levine, Norman. author. aut Link
VIII, 246 p.
Keywords: Marx's Rebellion Against Lenin, by negating the Leninist-Stalinist theory of dialectical materialism and tracing Marx's political philosophy to the Classical Humanism of Aristotle, overthrows the stultifying entrapment of Stalinist Bolshevism and contributes to the revitalization of Marx's method.